2002
DOI: 10.1038/sj.gene.6363876
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of innate immune responses against cytomegalovirus: MCMV meets its match

Abstract: Cytomegalovirus (CMV) is a widespread pathogen that is All Ly49 receptors characterized to date interact with MHC class I molecules on potential target cells, resulting in the accumulation of signals to the NK to either 'kill' or 'ignore' the cell based upon the repertoire of MHC class I molecules expressed. The identification of Cmv1 as Ly49H, a stimulatory member of the Ly49 family, adds an interesting twist to the Ly49 story. Although the ligand of Ly49H is not yet known, there is already compelling evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 150 publications
(138 reference statements)
0
26
0
Order By: Relevance
“…In addition, the degree of protection against vvHCV.S challenge after HCV-LP immunization are rather disparate between the two strains. This disparity is most likely due to the different genetic backgrounds, for the two strains have been shown to exhibit divergent cytokine responses and susceptibility to various infections (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the degree of protection against vvHCV.S challenge after HCV-LP immunization are rather disparate between the two strains. This disparity is most likely due to the different genetic backgrounds, for the two strains have been shown to exhibit divergent cytokine responses and susceptibility to various infections (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Using different strains of mice a susceptibility locus for CMV infection, cmv1, was identified and later shown to encode the Ly49 family of proteins (19). There are at least 14 members and most are expressed on NK and NKT cells, where the majority act as NK inhibitory receptors for MHC I molecules.…”
Section: Innate Immunitymentioning
confidence: 99%
“…In an important paper on the genetic control of innate immune responses against MCMV that appeared in your last issue, Drs JR Webb, S-H Lee and SM Vidal provide an interesting historical perspective of the MCMV infection model from its inception to the discovery of the gene responsible for the phenotype . 1 We have indicated already in 1974, 2 that the susceptibility of different strains of mice to MCMV infection is under genetic control, but our paper has probably escaped the attention of the authors. In the mentioned paper, we have reported that MCMV isolated from wild mice proved to be non-infectious for albino Swiss mice and could not be propagated in cell cultures derived from Swiss embryos.…”
mentioning
confidence: 89%